Taking Charge : Native American Self-Determination and Federal Indian Policy, 1975-1993 - Castile, George Pierre (Book collections on Project MUSE., 2006)
"Castile shows that, despite near-universal support, self-determination has suffered from problems arising from implementation, as turning policy into reality on the reservations has proved surprisingly difficult. He examines the challenge of sustaining "progress" in Indian self-determination because of funding problems, contract regulations, and the immovable nature of the federal bureaucracy. He also points to the instability of some tribal governments, along with apprehension among some Indians that self-determination would bring with it the abandonment of federal support for tribal existence."--Jacket.